Pseudoaneurysm of the dorsalis pedis artery: a case report (Research, Society and Development, 2021)
The article aims to report the case of a male patient with pseudoaneurysm of the dorsalis pedis artery, as well as to present the case management. A 76-year-old male patient with controlled arterial hypertension, a former smoker, was admitted complaining of a lump in the left foot and numbness in the toes. On physical examination, he had a pulsatile nodule on the dorsum of his left foot. The carotid and upper and lower limb pulses were normal. After suspicion of true aneurysm, left lower limb Arterial Doppler (LLL) was requested. Doppler ultrasound revealed aneurysmal dilatation in the dorsum left foot artery with a yin-yang image suggestive of pseudoaneurysm. Pedal aneurysmectomy was performed, as well as ligation and section of arterioles combined with pseudoaneurysm. The hemostasis was reviewed and, finally, the skin was synthesized with 4.0 nylon. At the end of the surgery, the patient's left foot motricity was preserved and there was no change in the perfusion of the left toes. Fifteen days after the surgical procedure, the stitches were removed and debridement of the edges was performed, observing the necrosis of small surgical wound edges. The patient is discharged, evolving with mild foot edema, but without other complications, good postoperative evolution.